The discover your true north fieldbook : a personal guide to finding your authentic leadership - George, Bill (William W.) (Wiley, 2015)
This Fieldbook both personalizes and unlocks the central lessons of its companion book, Discover Your True North by Bill George. It shares the most powerful insights that coauthors Nick Craig, Bill George, and Scott Snook have learned from helping more than 10,000 leaders discover and live up to their fullest potential. Each chapter contains potent exercises that help you mine your life story for deep insights and important patterns. As you work your way through these reflections, you will gain a clearer sense of who you are and why you lead--the essence of an authentic leader.